(untitled) (Journal of Civil Engineering Researchers, 2022)
One of the problems of common bracing system is their buckling against compressive loads, which reduces the amount of energy loss of the structure. Buckling Restrained Brace (BRB) have solved the problem of conventional braces by eliminating the overall buckling of the brace under pressure. Buckling Restrained Braced Frame (BRBF) is a new type of bracing system that has been widely used in recent years. Nowadays the use of buckling restrained braces, due to having more advantages compared to conventional steel braces, have received the attention of researchers and engineers that these advantages include: high ductility, more energy loss, no overall and local buckling, and also having a symmetrical cyclic curve. This type of bracing is considered as one of the effective systems for dealing with lateral loads caused by the earthquake. Disadvantages in the seismic behavior of conventional braces, such as ductility and low energy loss, general and local buckling, as well as having an asymmetric cyclic curve, have provided grounds for its modification or exclusion from the seismic design process. Buckling restrained braces are a type of energy loss system that, in addition to providing high lateral stiffness, increase the formability and energy loss of the structure. The use of this type of braces is allowed in the regulations of some countries. But in some other countries, including Iran, it has not been mentioned. According to the seismicity of the country and the increasing use of these structures in the world, the use and localization of this type of bracing system in Iran is inevitable, and the entry of this lateral bearing system into the design regulations, especially the earthquake regulations of Iran, is mandatory. The results of the analysis show that the energy loss capacity of the buckling restrained brace is about 5 times the energy loss capacity of the normal brace.